StrandAdvantage test for early‐line and advanced‐stage treatment decisions in solid tumors. (3rd April 2017) - Sen, Manimala; Katragadda, Shanmukh; Ravichandran, Aarthi; Deshpande, Gouri; Parulekar, Minothi; Nayanala, Swetha; Vittal, Vikram; Shen, Weiming; Phooi Nee Yong, Melanie; Jacob, Jemima; Parchuru, Sravanthi; Dhanuskodi, Kalpana; et al.
Abstract: Comprehensive genetic profiling of tumors using next‐generation sequencing (NGS) is gaining acceptance for guiding treatment decisions in cancer care. We designed a cancer profiling test combining both deep sequencing and immunohistochemistry (IHC) of relevant cancer targets to aid therapy choices in both standard‐of‐care (SOC) and advanced‐stage treatments for solid tumors. The SOC report is provided in a short turnaround time for four tumors, namely lung, breast, colon, and melanoma, followed by an investigational report. For other tumor types, an investigational report is provided. The NGS assay reports single‐nucleotide variants (SNVs), copy number variations (CNVs), and translocations in 152 cancer‐related genes. The tissue‐specific IHC tests include routine and less common markers associated with drugs used in SOC settings. We describe the standardization, validation, and clinical utility of the StrandAdvantage test (SA test) using more than 250 solid tumor formalin‐fixed paraffin‐embedded (FFPE) samples and control cell line samples. The NGS test showed high reproducibility and accuracy of >99%. The test provided relevant clinical information for SOC treatment as well as more information related to investigational options and clinical trials for >95% of advanced‐stage patients. In conclusion, the SA test comprising a robust and accurate NGS assay combined with clinically relevant IHC tests can detect somatic changes of clinical significance for strategic cancer management in all the stages. Abstract : A combined interpretation of results from next‐generation sequencing and immunohistochemistry/Microsatellite instability (IHC)/(MSI) tests in the genetic profiling of solid tumors provides a comprehensive report of superior clinical utility (96%) in comparison to NGS alone or traditional tests (single gene, IHC, MSI, FISH, etc.) currently available in the market. The analytical validation demonstrates high precision, reproducibility, and accuracy, while providing relevant information for both early and advanced cancer treatments.